Procalcitonin and Midregional Proatrial Natriuretic Peptide as Markers of Ischemic Stroke: The Northern Manhattan Study. Issue 7 (July 2016) - Katan, Mira; Moon, Yeseon P.; Paik, Myunghee C.; Mueller, Beat; Huber, Andreas; Sacco, Ralph L.; Elkind, Mitchell S.V.
Abstract : Background and Purpose—: Chronic infections and neuroendocrine dysfunction may be risk factors for ischemic stroke (IS). We hypothesized that selected blood biomarkers of infection (procalcitonin [PCT]), hypothalamic–pituitary–axis function (copeptin), and hemodynamic dysfunction (midregional proatrial natriuretic peptide [MRproANP]) are associated with incident IS risk in the multiethnic, urban Northern Manhattan Study (NOMAS) cohort. Methods—: A nested case–control study was performed among initially stroke-free participants. Cases were defined as first IS (n=172). We randomly selected controls among those who did not develop an event (n=344). We calculated Cox proportional hazards models with inverse probability weighting to estimate the association of blood biomarkers with risk of stroke after adjusting for demographic, behavioral, and medical risk factors. Results—: Those with PCT and MRproANP, but not copeptin, in the top quartile, compared with the lowest quartile, were associated with IS (for PCT adjusted hazard ratio [HR], 1.9; 95% confidence interval [CI], 1.0–3.8 and for MRproANP adjusted HR, 3.5; 95% CI, 1.6–7.5). The associations of PCT and MRproANP differed by stroke etiology; PCT levels in the top quartile were particularly associated with small vessel stroke (adjusted HR, 5.1; 95% CI, 1.4–18.7) and MRproANP levels with cardioembolic stroke (adjusted HR, 16.3; 95% CI, 3.7–70.9). Conclusions—: Higher levels of PCT, a marker of infection, and MRproANP, a marker for hemodynamic stress, were independently associated with IS risk. PCT was specifically associated with small vessel and MRproANP with cardioembolic stroke risk. Further study is needed to validate these biomarkers and determine their significance in stroke risk prediction and prevention.